Development and validation of a liquid chromatography–tandem mass spectrometry method for topotecan determination in beagle dog plasma and its application in a bioequivalence study. (21st June 2013) - Ye, Ling; Shi, Jian; Wan, Shanhe; Yang, Xiaoshan; Wang, Ying; Zhang, Jiajie; Zheng, Dayong; Liu, Zhongqiu
ABSTRACT Topotecan (TPT) is an important anti‐cancer drug that inhibits topoisomerase I. A sensitive and robust liquid chromatography–tandem mass spectrometry (LC‐MS/MS) method that potentially determines TPT in beagle dog plasma is needed for a bioequivalence study of TPT formulations. We developed and validated LC‐MS/MS to evaluate TPT in beagle dog plasma in terms of specificity, linearity, precision, accuracy, stability, extraction recovery and matrix effect. Plasma samples were treated with an OstroTM sorbent plate (a robust and effective tool) to eliminate phospholipids and proteins before analysis. TPT and camptothecin (internal standard) were separated on an Acquity UPLC BEH C18 column (1.7 µm, 2.1 × 50 mm) with 0.1% formic acid and methanol as the mobile phase at a flow rate of 0.25 mL/min. TPT was analyzed using positive ion electrospray ionization in multiple‐reaction monitoring mode. The obtained lower limit of quantitation was 1 ng/mL (signal‐to‐noise ratio > 10). The standard calibration curve for TPT was linear (correlation coefficient > 0.99) at the concentration range of 1–400 ng/mL. The intra‐day and inter‐day precision, accuracy, stability, extraction recovery and matrix effect of TPT were within the acceptable limits. The validated method was successfully applied in a bioequivalence study of TPT in healthy beagle dogs. Copyright © 2013 John Wiley & Sons, Ltd.